Development Of Generator Circuit For Electron Temperature And Density Probe (Tenep) For Mysat - Abdul Latif, Muhammad Aadam (Universiti Sains Malaysia, 2018)
Malaysia Youth Satellite (MYSAT) is a scientific CubeSat-based project initiated by School of Aerospace Engineering Universiti Sains Malaysia in 2016. The objective of the MYSAT mission is to measure electron density in E-layer of ionosphere. This mission is driven from a study which reported that earthquake precursors can be analysed from the ionosphere, which opens the possibility in predicting future earthquakes. It was found that one of the common features shown from ionosphere data measurement from several earthquakes is the electron density. Electron temperature and density probe (TeNeP) is an instrument developed based on DC Langmuir Probe that could help researchers studies the ionosphere to potentially predict future earthquakes. The device develops a technique by measuring current-voltage (I-V) characteristics of an electrode immersed in charged plasma particles. The I-V characteristic of the plasma will then be retrieved from the device where the plasma’s electron and ion density together with the temperature can be acquired. MYSAT, a Cube-Sat based on a 1U platform could contribute into this on-going research. Hence, an already developed TeNeP generator circuit based on a 2U platform needs to be redeveloped for MYSAT’s 1U based platform. Several performance tests are performed to the TeNeP generator circuit in the preparation of the MYSAT mission.